2013
DOI: 10.1186/1756-0500-6-276
|View full text |Cite
|
Sign up to set email alerts
|

Critical incidents in a tertiary care clinic for internal medicine

Abstract: BackgroundReducing medical errors has become an international concern. Population-based studies consistently demonstrate inacceptable high rates of medical injury and preventable deaths. Thus, electronic critical incident reporting systems are now increasingly used in hospitals, predominantly in anesthesia. However, studies systematically analyzing critical incidents are scarce. Our aim was to describe content and causes of critical incidents in our Clinic for Internal Medicine.ResultsWe retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
9
1
1
Order By: Relevance
“…Jenis insiden yang paling sering terjadi adalah kesalahan pengobatan (62%). Saat meresepkan 29% dan diikuti 26% komunikasi yang kurang tepat (Scharein & Trendelenburg, 2013).…”
Section: Pendahuluanunclassified
“…Jenis insiden yang paling sering terjadi adalah kesalahan pengobatan (62%). Saat meresepkan 29% dan diikuti 26% komunikasi yang kurang tepat (Scharein & Trendelenburg, 2013).…”
Section: Pendahuluanunclassified
“…Autolysin which can be found in all S. pneumococcal serotypes is the advantage of this gene compared to other genes so that this gene can be used as a target gene in detecting Streptococcus pneumoniae molecularly in detecting the causes of pneumococcal pneumonia and this is evident from the results of the study in table 6. it was seen that where the LytA gene can detect S. pneumoniae in a sample of pneumonia patients. And the LytA gene has also been used successfully to distinguish Streptococcus pneumoniae from S.viridans (Wu et al, 2015) Even so, molecular examination still has a weakness in detecting genes if the extracted sample is contaminated so that it can cause false positives or false negatives. Therefore, each check must be accompanied by positive and negative controls so that it is easier for us to interpret the correct and reliable results.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Gillespie et al (2013) found that a risk of harm was associated with poor interprofessional communication and teamwork. Shortcomings in communication and teamwork were also found to be a major cause of critical incidents (Scharein & Trendelenburg, 2013). Insufficient communication has been recognised as not only a source of incidents but also a cause of patients' suffering from health care (Berglund, Westin, Svanström, & Sundler, 2012).…”
Section: Discussionmentioning
confidence: 99%